Peran Pendidikan Agama Kristen dalam Mengatasi Dampak Penggunaan Teknologi bagi Remaja di era Digital - Nababan, Samuel; Sianturi, Emma; Rantung, Dyoys Anneke; Naibaho, Lamhot; Boiliu, Esti Regina (Harati: Jurnal Pendidikan Kristen, 2023)
This article discusses the significant role of Christian Religious Education in responding to the negative impacts of technology use on adolescents in the digital era. The research focuses on how religious principles, including inner peace, self-control, and meaningful goal-setting, provide a strong foundation for adolescents to confront technological challenges. The research methods involve analyzing the content of Christian religious teachings and case studies to comprehend the concrete impacts on adolescents. The findings affirm that Christian Religious Education can shape adolescent character, guide wise technology use, and provide moral foundations to address digital pressures. The discussion highlights the integration of religious values into adolescent life, the development of critical thinking skills towards digital information, and the strengthening of interpersonal relationships. The conclusion emphasizes the urgency of Christian Religious Education as a holistic solution, enabling adolescent growth in spiritual, moral, and emotional aspects amid the complexities of the digital era. Shaping character, guiding prudent technology use, and instilling moral values make Christian Religious Education key to assisting adolescents in navigating digital challenges with overall balance.